Similarity search and applications : 9th International Conference, SISAP 2016, Tokyo, Japan, October 24-26, 2016, Proceedings /: 9th International Conference, SISAP 2016, Tokyo, Japan, October 24-26, 2016, Proceedings. (2016) - Unknown
No abstract available